Impact of social-media marketing, price and perceived quality on brand loyalty amongst generation Y (Millennials) customers, a developing country perspective - Islam, Kazi Tasnimul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.